(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Here a case of osteoma is described situated in right mastoid part of temporal bone (post auricular region) in a 35-year-old female. The swelling was slow-growing, oval in shape, stony hard in consistency, 3cm x 5cm in size with normal & free overlying skin but fixed to the bone & non-tender. FNAC revealed no malignant cells. X-ray Mastoids Towne’s view showed right mastoiditis. CT scan findings were in favour of angular dermoid without bony erosion. Surgical excision was done under general anaesthesia. Histopathological report was osteoma. Postoperative period was uneventful and follow up after 10 days was fine. Key words: Osteoma; Temporal bone. DOI: 10.3329/bjo.v16i2.6851 Bangladesh J Otorhinolaryngol 2010; 16(2): 136-138